Analysing the critical factors influencing trust in e-government adoption from citizens' perspective: A systematic review and a conceptual framework. Issue 1 (February 2017) - Alzahrani, Latifa; Al-Karaghouli, Wafi; Weerakkody, Vishanth
Abstract: Although the success adoption of e-government contingent upon citizens' trust and their willingness to use it, little consideration has been paid to explore the adoption of e-government from citizens' trust perspective. This paper provides a critical and systematic review of the current literature on citizens' trust in e-government, with a particular focus on the most critical factors influencing citizens' trust in respect of the adoption of e-government. The extant literature was identified through six electronic databases, from 2000 to 2014. Academic articles were reviewed if they contained a relevant discussion of the antecedents or factors influencing citizens' trust in e-government adoption. The findings of this review reveal that several studies have been conducted in the area of trust in e-government (particularly trust in government and trust in the internet) with limited consideration paid to citizen's aspects of trust (such as personality, culture, gender, experience, education level, beliefs and value of systems). Based on the findings of the critical review, a conceptual framework is proposed by developing further the updated DeLone and McLean IS Success Model, which presents the antecedents of trust in e-government adoption.